Imagining communities in Thailand : ethnographic approaches - Tanabe, Shigeharu (Chiang Mai, Thailand : Mekong Press, 2008)
"Este libro se origina del simposio internacional" : Imagining communities in Thailand : etnographic approaches", celebrado el 17-18 de noviembre de 2003, en el Museo Nacional de Etnología, Osaka, Japón" -
Introduction: Imagined and imagining communities / Shigeharu Tanabe -- Nr. 1. Policing the imagined family and children in Thailand : from family name to emotional love / Thanes Wongyannava -- Nr. 2. An "imagining" community : the case of Sisa Asoke, Si Sa Ket province / Kanoksak Kaewthep -- Nr. 3. Constructing and maintaining the Ta-la-ku community : the Karen along the Thai-Myanmar border / Kwanchewan Buadaeng -- Nr. 4. Making sense of place : a case study of vendors and small entrepreneurs in the Chiang Mai night bazaar / Apinya Fuengfusakul -- Nr. 5. The romantic ethic and the notion of modern society : imagining communities among northern Thai factory women / Kyonosuke Hirai -- Nr. 6. Suffering, community, and self-government : HIV/AIDS self-help groups in northern Thailand / Shigeharu Tanabe -- Reflections: Imagined and imagining communities / Roger Goodman.
Rincón tailandés.
Incluye referencias bibliográficas (páginas [195]-209) e índice.
Keywords: GRUPOS SOCIALES -- TAILANDIA -- CONGRESOS, CONFERENCIAS, ETC; DESARROLLO DE LA COMUNIDAD -- TAILANDIA -- CONGRESOS, CONFERENCIAS, ETC; ETNOLOGIA -- TAILANDIA -- CONGRESOS, CONFERENCIAS, ETC; ANTROPOLOGIA -- TAILANDIA; TAILANDIA -- CONDICIONES SOCIALES